Grinding comparative analysis between different proportions of water-oil applied to MQL technique and industrial production cost towards a green manufacturing - Lopes, Jose Claudio [UNESP]; Avila, Benicio Nacif [UNESP]; Souza Rodrigues, Matheus de [UNESP]; Garcia, Mateus Vinicius [UNESP]; Ribeiro, Fernando Sabino Fonteque; Mello, Hamilton Jose de [UNESP]; Sanchez, Luiz Eduardo De Angelo [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer, 2021)
The high temperatures involved in the grinding process require an efficient lubri-refrigeration method. Currently, the conventional method (flood) is the most used in industries. However, this method comes up against environmental damage and the health of operators, due to high amounts of fluid injected into the cutting region. Therefore, the use of the minimum quantity lubricant (MQL) technique with a wheel cleaning jet (WCJ) proves to be a viable alternative. This work makes a comparative analysis of the MQL + WCJ system with a conventional method. In this sense, the experiments grinding the AISI 4340 steel with an aluminum oxide wheel. The lubrication and cooling of the process were done by the conventional method, pure MQL, and diluted MQL (oil-water 1:1, 1:3, 1:5) with and without cleaning (WCJ). The output parameters evaluated were surface roughness (Ra), roundness error, G-ratio, tangential cutting force, specific energy, microstructure, and cost. The surface roughness shows an increase of only 18%, with the use of the MQL technique diluted 1:5 + WCJ compared to the conventional method. Also, the implementation of the MQL technique is cheaper than the conventional method. The results show that the addition of water in MQL favors grinding, and the efficiency of MQL increases when associated with WCJ for all parameters.
Keywords: Cylindrical grinding; Diluted MQL; WCJ; AISI 4340 steel; Aluminum oxide wheel